ACCOUNTING TREATMENT AND LEGISLATION OF LEASING ARRANGEMENTS - Selma Novalija; Hamid Mutapčić; Elmira Kovač (Economic Review)
Companies are not always able to purchase fixed assets required to start, expand or modernize their own operations, and also do not have adequate resources that could offer as security for bank loans. Leasing is the answer to such problems, as it provides the possibility of leasing recipient to obtain the necessary equipment. Company pays lease fees from the profits generated from leasing subject use. Leasing, as a contemporary form of funding from year to year, plays a more prominent place in the international business world, making it necessary to devote special attention to the legislation and accounting coverage of business changes, which occur while taking and giving funds to leasing. The importance of these issues in accounting, or financial reporting is confirmed by the fact that International Accounting Standard (IAS) 17 Leases is dedicated to this aspect.